An ethnobotanical study of medicinal plants used by ethnic communities of Nuapada District, Odisha to treat periodontal disorders - Binapani Barik; Pattnaik, Gurudutta; Bhabani Sankar Satapathy; Biswajeet Acharya; Ladi alik kumar (Ethnobotany Research and Applications, 2024)
Background: The herbal remedies commonly employed in the management of dental disorders have antimicrobial, anti-inflammatory, analgesic, and astringent characteristics. Antibacterial plant species can prevent tooth decay and bacterial growth. Despite the fact that ethnobotanical knowledge offers insightful perspectives on conventional thought, scientific inquiry and secure dental disease treatments, some cultures have established specific customs related to the use of botanical specimens for oral hygiene. The study’s main goal was to document Nuapada’s indigenous people’s ethnomedicinal uses of plant species to treat periodontal disorders. Methods: Questionnaires in local languages were used to collect information from 30-80-year-olds in multiple locations. The survey covered each recommended plant’s component, therapeutic uses and preparation. Study findings were analyzed using frequency of citation (FC), relative frequency of citation (RFC), cultural importance index (CI), informant participants (IP), informant response (IR) and use report (UR). Results: The outcomes of the investigation proved that Azadirachta indica showed the highest RFC and highest CI value of 0.96 among the plants that were investigated. The plant species Ocimum basilicum , Curcuma longa and Withania somnifera also showed a significant RFC value of 0.90, 0.89, and 0.87, respectively. The CI of each plant lies in its therapeutic value, as it offers a pharmacological approach for treating dental disorders. Conclusions: The above ethnobotanical surveys conclude that Azadirachta indica is widely recognized as a traditional medicinal plant with significant potential for treating dental disorders, as compared to other plant species. Keywords: Ethnobotanical Study, Nuapada District, Medicinal Plants, RFC, CI, Oral Diseases